Detection of icaA Gene Expression in Clinical Biofilm-Producing Staphylococcus Aureus Isolates - Mohammed, Shaimaa W.; Radif, Hala M. (Iraqi Journal of Science, 2020)
The pathogenicity resulting from Staphylococcus aureus infection has remarkable importance as one of the community-associated bacterial infections, due to the virulent ability of these bacteria to produce biofilms. This study was designed to detect biofilm production in clinical isolates from samples of wounds and urinary tract infections. The expression levels of the icaA gene that is responsible of slime layer production in biofilms was compared in isolates with different biofilm producing capabilities. Fifty seven samples that included 32 samples from urine and 25 samples from wounds were collected from Alwasti Hospital, Al-Kindi Teaching Hospital, and Alzahraa Clinic, Baghdad, Iraq. The bacteria was identified according to biochemical tests, API20 strip test, and PCR assay. The results of 16S rRNA PCR detection revealed that nine isolates were identified as S. aureus. The biofilm assay showed that 46.15% of the isolates were strong biofilm producers, 46.15% had moderate ability to produce biofilm, and 7.70% were weak producers. Quantitative PCR assay was carried out on three isolates with different biofilm-producing abilities. The results demonstrated that the strong biofilm-producing isolates had significantly higher (P â‰¤0.01) gene expression level (6.508) compared with the moderate (1.624) and the weak (1.231) isolates.